Гуманізм, народність та природовідповідність – визначальні принципи педагогічної системи К. Д. Ушинського - Марчук, Сергій; Чемерис, Ірина (Східноєвропейський національний університет імені Лесі Українки, 2018)
У статті науково обґрунтовано основні положення виховної системи К. Д. Ушинського – гуманізм, народність, природовідповідність. З‟ясовано шляхи їх реалізації, визначені у психолого-педагогічних працях видатного педагога. Доведено важливість концептуальних положень педагогічної системи К. Д. Ушинського в контексті сучасного освітнього середовища, адаптації їх до нових потреб шкільної практики сьогодення. Важливою є думка К. Д. Ушинського, що народ є справжнім захисником батьківщини, успіхом її благ і досягнень, носієм найвищої людської якості – гуманізму. In the article, the basic theories of K. D. Ushynskiy‟s educational system – humanism, ethnics, natural correspondence are scientifically approved. The implementation ways of the principle of humanism in the K. D. Ushynskiy‟s pedagogy are: the development of humane human characteristics; behavior by the rule: “Do not do to others what you would be upset by”; a humane attitude towards the people around us (namely such an attitude in which we consider ourselves as “we are not higher or lower than other people”, to teach the child to worry about the mental state of other people, to put yourself in the place of offended person and feel what he should feel . The teacher justified the idea of ethnics, the essence of which is reflected in such thoughts of Ushynskiy: people without ethnics – a body without soul; each nation has its own special national system of education, and therefore one nation‟s borrowing of educational systems from another one is impossible; you can‟t live on the model of another nation; the language of people is integral and organic their creation. The substantiation of the principle of natural correspondence in the K. D. Ushynskiy‟s pedagogy – is the consideration of the natural features of the child's organism, its age-long, individual, and sexual characteristics in the process of education. The importance of the conceptual theories of K. D. Ushynskiy‟s pedagogical system is proved in the context of the modern educational environment, their adaptation to the new needs of school practice nowadays. The K. D. Ushynskiy‟s opinion that the nation is a real defender of the homeland, a success of its benefits and achievements, a bearer of the highest human quality – humanism is important.
Keywords: К. Д. Ушинський; гуманізм; народність; природовідповідність; принцип; педагогічна система